2017
DOI: 10.1016/j.ejrad.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Residual tumour detection in post-treatment granulation tissue by using advanced diffusion models in head and neck squamous cell carcinoma patients

Abstract: Conclusion: DWI parameters obtained by advanced fitting models will be one of the diagnostic tools for the detection of residual tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Several previous studies evaluated the utility of DWI in differentiating posttreatment changes from recurrence and concluded that DWI showed high diagnostic performance. 7,11,[13][14][15][16] Morphologic imaging features for LTR described in previous literature included infiltrative mass appearance, with intermediate to high SI in T2 WIs and postcontrast enhancement. However, these features could overlap with those of benign posttreatment findings such as posttherapy inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies evaluated the utility of DWI in differentiating posttreatment changes from recurrence and concluded that DWI showed high diagnostic performance. 7,11,[13][14][15][16] Morphologic imaging features for LTR described in previous literature included infiltrative mass appearance, with intermediate to high SI in T2 WIs and postcontrast enhancement. However, these features could overlap with those of benign posttreatment findings such as posttherapy inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that bi-exponential fitting of the apparent diffusion co-efficient values on diffusion-weighted MRI were significantly lower in patients with residual tumours compared to those without tumour 25 . Lastly, advanced diffusion fitting models such as diffusion kurtosis imaging and the stretched exponential model are the diagnostic tools for detecting residual tumours in post-treatment granulation 26 …”
Section: Discussionmentioning
confidence: 99%
“…Second, we utilised the calculation of tumour blood flow. Applications of advanced post-processing techniques for tumour blood flow, with the creation of parametric blood flow maps, and use of diffusion tensor imaging or kurtosis imaging, will improve the results 26 , 30 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation